2018
DOI: 10.1097/wno.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Optic Neuropathy

Abstract: Herpes zoster optic neuropathy is an unusual but distinctive complication of HZO. Visual recovery after HZON is variable. Identification of an optimal treatment regiment for HZON could not be identified from our patient cohort. Systemic antiviral agents are a component of HZON treatment regimens. Efficacy of systemic corticosteroids for HZON remains unclear and should be considered on a case-by-case basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Systemic corticosteroids are also indicated for facial palsy, cranial polyneuritis, and severe inflammatory ocular complications. Topical corticosteroids treat disciform keratitis, endotheliitis, anterior uveitis, and optic neuropathy [5], [16]. However, the use of corticosteroid is controversial because it will increase risk of ocular complications, thinning and perforation of cornea, secondary glaucoma, and reactivated dendriform keratitis [5].…”
Section: Treatmentmentioning
confidence: 99%
“…Systemic corticosteroids are also indicated for facial palsy, cranial polyneuritis, and severe inflammatory ocular complications. Topical corticosteroids treat disciform keratitis, endotheliitis, anterior uveitis, and optic neuropathy [5], [16]. However, the use of corticosteroid is controversial because it will increase risk of ocular complications, thinning and perforation of cornea, secondary glaucoma, and reactivated dendriform keratitis [5].…”
Section: Treatmentmentioning
confidence: 99%
“…It has been suggested that early treatment with antivirals has a better outcome. [ 9 ] Our patient presented 2 days after experiencing visual loss and ptosis. Earlier institution of intravenous acyclovir might have improved the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…HZO is known to occur more frequently in patients with immunosuppression. [ 8 ] Despite a few anecdotal reports,[ 1 3 6 9 ] it has not been proven conclusively that OAS secondary to HZO occurs more commonly in immune deficient patients. It has been suggested that early treatment with antivirals has a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing evidence that antiviral therapy combined with systemic corticosteroids may be more effective in treating the sequelae of HZO [11]. In a recent retrospective study, 9 of 12 patients with HZO-related optic neuropathy experienced improved visual outcomes after receiving adjuvant corticosteroid therapy [12]. Furthermore, there are multiple reports of delayed onset ophthalmoplegia after antiviral treatment, indicating that antiviral therapy alone may not be sufficient to prevent the neurologic complications of HZO [13].…”
Section: Discussionmentioning
confidence: 99%